2006
DOI: 10.2166/wh.2006.043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil depth and texture on fecal bacteria removal from septic effluents

Abstract: This study evaluated the effectiveness of soils with different texture and depth to treat fecal bacteria eluted from a house-hold septic effluent. The assessments were accomplished by leaching undisturbed soil monoliths of 30, 45, and 60cm thickness and 25cm in diameter, representing the four different textural groups and hydraulic loadings recommended by the Kentucky Health Department, with domestic wastewater effluent collected regularly from a house-hold septic system. Eluent concentrations were monitored d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Therefore, the vadose zone was on average over 1.6 m thicker beneath Field 2 relative to Field 1 at JWS. Prior studies have shown that bacteria treatment typically improves as the unsaturated zone thickness increases [7,8,12,14,15,26]. Therefore, there was likely more bacterial filtration beneath Field 2, relative to Field 1.…”
Section: Microbial Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the vadose zone was on average over 1.6 m thicker beneath Field 2 relative to Field 1 at JWS. Prior studies have shown that bacteria treatment typically improves as the unsaturated zone thickness increases [7,8,12,14,15,26]. Therefore, there was likely more bacterial filtration beneath Field 2, relative to Field 1.…”
Section: Microbial Distributionmentioning
confidence: 99%
“…OWS installed in soils with higher percentages of fine-textured materials such as silt and clay, typically are more efficient at reducing microbial concentrations than OWS installed in sandy soils, due to the increased reactive surface area and residence time [7,14,15]. Research has also suggested that higher wastewater loading rates may lead to decreased treatment [8,[16][17][18] and that OWS that utilize low pressure pipe (LPP) distribution can more efficiently treat wastewater constituents such as bacteria relative to gravity flow effluent distribution systems [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with other studies in which the removal efficiency of fecal bacteria in the STA was investigated in relation to soil texture and depth (e.g., Karathanasis et al, 2006; Amador et al, 2009). The positive correlation between bacteria removal and depth points to mechanical filtration (straining) processes that are most pronounced in finer textured soils (Keswick and Gerba, 1980; Powelson et al, 1990). Finer textured soils have smaller pores and lower hydraulic conductivity, which promotes the mechanical filtration of bacteria and attachment.…”
Section: Resultsmentioning
confidence: 99%
“…A first order reliability methods algorithm (FORM) was used to model the fate and transport of benzene in groundwater (Kim et al, 2006b). Removal of nutrients from septic tank effluents was found to be related to soil texture, with coarse grained soils having the poorest removal (Karathanasis et al, 2006a). A minimum thickness of 60 cm was found to provide consistent compliance with EPA standards for BOD, ammonia, and total-phosphorous removal efficiency.…”
Section: Szna Sustainable?mentioning
confidence: 99%